Wearable authentication device with biometrical intrusion prevention system - Magalhães, Paulo Sérgio Tenreiro (2005)
The biometric technologies have been widely used for authentication purposes. But the current needs for security creates the challenge of avoiding attacks before they take place. This can be achieved by combining the traditional biometric technologies with algorithms/tools capable of managing the existing knowledge about emotion recognition. This area has been developed essentially to support the implementation of robots, and for lies detection, and a lot of sensors are already defined and/or proposed to support it. However, in order to use them for real-time human emotion recognition applications, those sensors must be made ubiquitous, non-intrusive and wireless. Besides, given the private nature of the information involved, such a system requires a safe environment for secure storing and processing the user information, like biometric patterns, what SmartCards with processing capabilities can provide. The development of a system so complex requires the development of the biometric algorithms adapted for this purposes, the development of emotions recognition multimodal algorithms and the integration of the resulting components (hardware and software) in a nonintrusive and easy way. In this paper we present the adaptation of a keystroke dynamics algorithm for use in intrusion prevention and we propose a biometrical intrusion prevention system, integrated in a wearable way through the development of a multifunctional textile structure that can supply power to the required microelectronics, while insuring comfort in use. The multifunctional textile structure, besides being comfortable, breathable and washable, has also an active role in assuring the well being of the user once it uses PCM – Phase Change Materials – to keep the user from feeling either cold or hot. Finally, as a probe of concept, it is described a possible application in a healthcare unit (where information security is critical).